Annotated record of the detailed examination of Mn deposits from R/V Argo SCAN IV Expedition stations in preparation for a DSDP survey in the Mariana Area (DSDP Leg 6, Site 53) - Dan Karig (PANGAEA, 1971)
During the fourth and fifth legs of Scan Expedition, drill Sites 53 and 60 were surveyed and Site 59 was traversed. In addition to the drill site surveys, several other areas across the Mariana Arc System were investigated in some detail, guided by reconnaissance work aboard the R/V Argo from the previous year. The remarkable similarities in the occurrence and relative positions of a wide range of structural features in western Pacific arc systems strongly suggest a common mechanism of origin. The area in which crustal deformation related to island arc tectonism is occurring, more extensive and complex than generally recognized, is defined as the active island arc system; this includes not only the trench and volcanic chain, but also the deep basin and submarine ridge on the concave side of the active volcanoes.
Supplement to: Karig, D (1971): Site Surveys in the Mariana Area (Scan IV). In: Fischer, A.G.; et al., Initial Reports of the Deep Sea Drilling Project, 6, Initial Reports of the Deep Sea Drilling Project, 6, U.S. Government Printing Office, VI, 681-689, https://doi.org/10.2973/dsdp.proc.6.120.1971